ORGANIZATIONAL PROCEDURES USED BY COMPANIES FOR LABOR MAINTENANCE - Augusto, Emerson Aparecido; Obregão, Fernando Dresch (Revista Interface Tecnológica, 2023)
The chosen theme “Organizational Procedures used by companies to maintain workforce” arose from the interest in finding out what the Human Resources areas have done to keep professionals within the organization. The objective of this work is to identify which programs and benefits are being offered by important industrial companies in the city of Araraquara, for the maintenance and loyalty of this workforce. The study involved a company in the metallurgical segment, which provides relevant subsidies for the execution of this work. The research was descriptive and had the objective of quantitatively analyzing the variables involved in the phenomenon of manpower maintenance in organizations. In general, organizations suffer from not having qualified labor in their staff, because this problem ends up harming the quality of products, the acquisition of new technologies and even the development of new products, seeking external solutions to achieve meet such a need. It is concluded at the end of this work that the result achieved meets the initial expectations, where it is expected to identify the benefits and existing programs.
Keywords: Strategies; Organizational Procedures; Maintenance; Human Resources